Willingness follow covid-19 vaccination pandemic conditions pregnant women family support - Nita Dwi Asikasari; Anggrawati Wulandari; Retno Palupi Yonni Siwi; Ferida Ugi Astuti (Science Midwifery, 2023)
COVID-19 vaccination for pregnant women is a strategic instrument to prevent transmission, reduce the risk of serious illness, and reduce maternal and infant mortality. Family support is an attitude, action, and acceptance of the family towards family members who are seen as an inseparable part where family members are always ready to provide assistance and assistance if needed. Objective: The purpose of this study was to analyze the relationship between willingness to participate in COVID-19 vaccination during the pandemic in terms of family support for pregnant women in the working area of Sampung Public Health Center, Ponorogo Regency. Metode this research is a cross sectional study. The sample in this study was pregnant women aged 13-33 weeks who had not been vaccinated against COVID-19 in the working area of the Sampung Public Health Center, Ponorogo Regency in July 2022 as many as 45 people using simple random sampling technique. Statistical test chi-square with a significant level of = 0.05.The results showed that 68.9% of respondents stated that they received good family support and 66.7% of respondents stated that they were willing to participate of vaccination. The results of the chi-square obtained that the chi (32.402) is greater than the chi table (3.841), it shows that good family support has an effect on vaccine availability. Family support and willingness to take the vaccine in pregnant women have a strong relationship, with test value of 0.647. Good family support can affect vaccination participation in pregnant women.